Uncovering research trends in family business studies through bibliometric analysis - Karim Azizi; Stefanus Rumangkit; Yan Aditiya Pratama; Antonius Satria Hadi; Muhamad Zulkiflee Osman (PHINISI, 2026)
This study aims to provide a comprehensive bibliometric analysis of family business literature, identifying emerging trends, key themes, and influential research clusters that have shaped its development. The research seeks to bridge the gap in existing literature by offering a systematic mapping of the field’s intellectual structure, revealing fragmentation, and proposing future directions. The study utilizes data sourced from the Scopus database, covering articles published between 2010 and 2026. A bibliometric approach was employed using the PRISMA framework for article selection and VOSviewer software to analyze key indicators such as publication trends, keyword co-occurrences, and citation performance. The analysis highlights the top 10 journals contributing to family business research, with the Journal of Family Business Management leading as the primary publication hub. Additionally, it identifies the countries with the highest publication and citation counts, with India and the United Kingdom taking the lead in global impact. Co-occurrence and clustering analysis further reveal three distinct research clusters focusing on the structural foundations (governance and succession), methodological landscapes, and internal drivers such as socioemotional wealth and innovation. The study also identifies future research areas such as corporate governance, social capital, innovation, and socioemotional wealth, which are critical for advancing the field. The findings contribute to a better understanding of the family business research trajectory and offer valuable insights for scholars, policymakers, and practitioners aiming to enhance the sustainability and professionalization of family-run enterprises.